The significance of gender and sexuality : a study of discrimination and equal employment opportunities policy in the state sector : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University - Raven, Anthea (Massey University, 1991)
The purposes of this study are twofold. The first is to look at the experiences of lesbian social workers in order to describe the themes and patterns characteristic of discrimination within the context of their professional and employment status in the state sector. The second is to examine whether the policy of Equal Employment Opportunities for women in the Department Of Social Welfare adequately addresses discrimination against lesbians, and the extent to which the needs of lesbians can be met within the existing framework of the policy. It has been proposed in this study that discrimination against lesbians in the workplace is a real and tangible source of oppression termed 'heterosexism'. Lesbian social workers' employment experiences indicate that these are qualitatively different from those of heterosexual women. Analysis of these experiences relies upon an understanding of the historical social, sexual and economic dynamic of male power over women. Heterosexuality has been emphasised as the only acceptable sexuality and therefore, an institutionalised form of control over all women's lives. One of the consequences of this control is the denial of the existence of lesbianism. This is because lesbianism represents an independent and alternative lifestyle and family structure. While this threatens the traditional male defined nuclear family relations it also challenges the view that women should be treated as economically dependent upon a man. There is strong evidence to suggest that gender is a significant determinant of employment opportunities. Thus, there is a clear basis for recognising women as a target group for special attention under an Equal Employment Opportunities policy. However, this study challenges the assumption that the needs of all women can be adequately addressed within the context of a hetero-relational model. For example, it is argued here that the underlying criteria for access to employment opportunities is based on conformity to traditional gender roles and stereotypes. This reinforces women's economic dependency on a man and a male controlled labour market. The view that women's equality should depend on their social, sexual and economic relations with men is therefore questioned. In contrast it is argued that lesbians should be able to benefit from their social, sexual and economic independence from a man and that any measure of their employment position in relation to men is a measure for all women. The radical potential for Equal Employment Opportunities policy for all women may well depend upon the inclusion of lesbians and their legal protection from discrimination.
Keywords: Women Civil Service; Lesbians; Employment; New Zealand